Atención regionalizada del trauma : una propuesta metodológica desde la dinámica de sistemas (2009)
ABSTRACT: Studies relating to trauma are mainly multicausal, but when we observe the impact of interventions on their causes, there is no clarity about the best way for prevention and control. Objective: To approach the problem of trauma from an integral point of view that facilitates understanding the phenomenon from its complex interrelationships. Methodology: using the system dynamics raised by Forrester to propose a dynamic model capable of predicting situations related to prevention and care, to raise public policies towards reducing the incidence and mortality. The process included six steps of the dynamics of systems to deliver a model for the analysis of existing and potential scenarios in their care, based on simulations of the behavior of the trauma, including the incidence and prevention of variables in interaction with prehospital care and hospitable. Results: the proposal was ideal in the care of trauma described in the dynamic scenario put “appropriate care of the patient described in the appropriate institution, is guaranteed to reduce the mortality for trauma”.